Study of the Predictive Validity of the Special Examination for the Students’ Admission to the Psychology Program - Gallardo Rayo, Iris; Álvarez Aguirre, Yolanda; Rojas Gorigoytia, Mónica (Revista de Psicología, 2003)
In order to evaluate the predictive validity of the admission special examination tests for students entering the Psychology program at the University of Chile, a follow up study of 121 students was carried out during two consecutive years. The results showed, according to the hypotesis, that a significant proportion of students had lower indicators of mental disorders, as compared to the percentage of a referent population, (15.9%). An analysis of the different instruments used at this examination (such as tests, interviews and focus groups), showed that the Zulliger test most significantly contributed to this mental disorder prediction in students.